Efficient oxidative dehydrogenation of ethanol by VOx@MIL-101: On par with VOx/ZrO2 and much better than MIL-47(V) - Bulánek, Roman; Čičmanec, Pavel; Kotera, Jiří; Boldog, István (Elsevier Science BV, 2019)
The possibility to apply metal organic framework (MOF) based catalysts for oxidation reaction in gas phase was explored. Catalytic activity of the vanadium oxide catalyst incorporated in MIL-101(Cr) as support was investigated in gas phase ethanol oxidative dehydrogenation (EtOH-ODH) and compared to that of MIL-47(V) metal organic framework material containing vanadium as central metal in the framework structure and to a classical VOx/ZrO2 supported vanadium oxide catalyst. It was found that vanadium species, incorporated in MIL-101(Cr) support by a variant of vapor deposition method, are stabilized in the form of well dispersed VOx species (no vanadium pentoxide clusters was detected in the catalyst). The obtained VOx@MIL-101(Cr) catalyst exhibited high selectivity towards acetaldehyde (up to 99%) at reaction temperatures not exceeding 200 degrees C. The catalytic activity of VOx@MIL-101(Cr) catalyst reached an activity level comparable to that of the classical VOx/ZrO2 catalyst, but the specific productivity of acetaldehyde (3 kg(AA) kg(cat)(-1) h(-1)) was higher by 75% compared with productivity on VOx/ZrO2 due to much higher content of vanadium species, which could be hosted by the MOF. On the other hand, MIL-47(V) catalyst exhibited negligible activity seemingly due to coordinatively saturated character of the vanadium centers and/or too high stability of the V-IV oxidation state. This proof-of-concept study proved that application of MOF materials as host matrices for heterogeneous catalysts aiming oxidation reaction in gas phase could be efficient as demonstrated on the example of oxidative dehydrogenation of ethanol.
Účinná oxidativní dehydrogenace etanolu pomocí VOx@MIL-101: srovnatelná s VOx/ZrO2 a mnohem lepší než MIL-47(V)
Keywords: Oxidative dehydrogenation; Vanadium; Ethanol; Acetaldehyde; MIL-101; MOF; oxidativní dehydrogenace; vanad; etanol; acetaldehyd; MIL-101; MOF